Editorial: Citizen Science and Social Innovation: Mutual Relations, Barriers, Needs, and Development Factors - Andrzej Klimczuk; Egle Butkeviciene; Minela Kerla (Frontiers in Sociology, 2022)
The presented Research Topic explores the potential of citizen science to contribute to the development of social innovations. It sets the ground for analysis of mutual relations between two strong and embedded in the literature concepts: citizen science and social innovation. Simultaneously, the collection opens a discussion on how these two ideas are intertwined, what are the significant barriers, and the need to use citizen science for social innovation.
Keywords: D83; L17; O35; Z13; 330; citizen science; co-creation; co-production; open science; participatory research; social innovation